Risky Gifts and Uncertain Business: A Discussion of Results from a Survey on Commissioning in New Music - Fryberger, Annelies; Lorenzon, Matthew (Circuit, 2016)
What are the risks involved in commissioning new music? Through interviews with 24 commissioners, performers, and composers based in Canada, the us, Australia, and France, we develop a model of the different types of risk encountered during the commissioning process. Despite providing the money for a commission, we found that commissioners are least exposed to financial risk as it is classically defined; commissioning fees really do behave like the philanthropic gifts they are legislated to be. Composers were likewise little exposed to financial risk, concerning themselves instead primarily with the uncertainty inherent to the creative process. We found that it is actually performers who are most exposed to financial risk, especially when they act as “middlemen” between commissioning bodies and composers. Burdened with compliance to a variety of Occupational Health and Safety laws and cash-flow issues stemming from conflicting outcomes and funding schedules, we found that performers were caught in a pincer between composers’ desires to take aesthetic risks and the obligations created by the philanthropic gift.